Reduced Slc1a1 expression is associated with neuroinflammation and impaired sensorimotor gating and cognitive performance in mice: Implications for schizophrenia. - Parisa Afshari; Wei-Dong Yao; Frank A Middleton (PLoS ONE, 2017)
We previously reported a 84-Kb hemi-deletion copy number variant at the SLC1A1 gene locus that reduces its expression and appeared causally linked to schizophrenia. In this report, we characterize the in vivo and in vitro consequences of reduced expression of Slc1a1 in mice. Heterozygous (HET) Slc1a1+/- mice, which more closely model the hemi-deletion we found in human subjects, were examined in a series of behavioral, anatomical and biochemical assays. Knockout (KO) mice were also included in the behavioral studies for comparative purposes. Both HET and KO mice exhibited evidence of increased anxiety-like behavior, impaired working memory, decreased exploratory activity and impaired sensorimotor gating, but no changes in overall locomotor activity. The magnitude of changes was approximately equivalent in the HET and KO mice suggesting a dominant effect of the haploinsufficiency. Behavioral changes in the HET mice were accompanied by reduced thickness of the dorsomedial prefrontal cortex. Whole transcriptome RNA-Seq analysis detected expression changes of genes and pathways involved in cytokine signaling and synaptic functions in both brain and blood. Moreover, the brains of Slc1a1+/- mice displayed elevated levels of oxidized glutathione, a trend for increased oxidative DNA damage, and significantly increased levels of cytokines. This latter finding was further supported by SLC1A1 knockdown and overexpression studies in differentiated human neuroblastoma cells, which led to decreased or increased cytokine expression, respectively. Taken together, our results suggest that partial loss of the Slc1a1 gene in mice causes haploinsufficiency associated with behavioral, histological and biochemical changes that reflect an altered redox state and may promote the expression of behavioral features and inflammatory states consistent with those observed in schizophrenia.